The Narrative Style of Randai in the Film Rantau - Adri Yandi; Ranang Agung Sugihartono; Pande Made Sukerta (Pascasarjana Institut Seni Indonesia Padang Panjang, 2025)
This article investigates the structural translation of the Minangkabau performative tradition of randai into cinematic language through a practice-led research framework. Departing from representational or thematic adaptation, the study positions randai as an organizing principle that shapes the narrative architecture, temporality, and audiovisual rhythm of the film Rantau. Core performative elements, such as dendang, galombang transitions, episodic composition, circular staging, and the mediating function of the Janang, are operationalized as structural devices rather than ethnographic references. The article adopts practice led research approach, a reflective and cyclical creative process integrating observation, interviews, textual study, scripting, performance translation, and editing. Editing is conceptualized as an epistemological site where meaning emerges through montage, temporal layering, and audiovisual juxtaposition. The resulting film employs a dual narrative system, linear within performative segments and non-linear within cinematic sequence, producing stratified temporality that articulates generational reinterpretations of merantau (migration). The findings demonstrate that performative tradition can be translated structurally into contemporary film without hierarchical subordination. The study contributes to discourses on intermediality, artistic research, and decolonial aesthetics by repositioning tradition as a generative epistemic framework within audiovisual production, while proposing a model for culturally grounded cinematic innovation.